Do network centrality measures predict dental outcomes of Indigenous children over time?. Issue 5 (3rd December 2020) - Soares, Gustavo Hermes; Santiago, Pedro Henrique Ribeiro; Biazevic, Maria Gabriela Haye; Michel‐Crosato, Edgard; Jamieson, Lisa
Abstract: Background: Centrality measures identify items that are central to a network, which may inform potential targets for oral interventions. Aim: We tested whether centrality measures in a cross‐sectional network of mothers' baseline factors are able to predict the association with children's dental outcomes at age 5 years. Design: A network approach was applied to longitudinal data from a randomised controlled trial of dental caries prevention delivered to 448 women pregnant with an Indigenous child in South Australia. Central items were identified at baseline using three centrality measures (strength, betweenness, and closeness). Centrality values of mothers' outcomes were regressed with their predictive values to dental caries experience and dental service utilisation at child age 5 years. Results: Items of oral health self‐efficacy and oral health literacy were central to mothers' baseline network. Strength at baseline explained 51% and 45% of items' predictive values to dental caries experience and dental service utilisation at child age 5 years, respectively. Adjusted and unadjusted values of node strength for the children's oral health network were highly correlated. Conclusion: Strength at baseline successfully identified mothers' items with greater importance to dental caries experience and dental service utilisation at child age 5 years.